The Moral Nature of Man in Organizations: A Comparative Analysis: Comment - Hellreigel, Don (Academy of Management Journal, 1971)
The article presents the author's opinions regarding the article ?The Moral Nature of Man in Organizations: A Comparative Analysis,? by William G. Scott and David K. Hart, published in the June 1971 issue. According to the author, some of the statements made by Hart and Scott regarding scientific management are inaccurate. The author goes on to contest Hart and Scotts? use of the concept of determinism in an organizational setting.